Resistance: righteous rage in the age of #MeToo - Goyette, Sue (University of Regina Press, 2021)
"Writers across the globe speak out against sexual assault and abuse in this powerful new poetry anthology, edited by Sue Goyette. These collected poems from writers across the globe declare one common theme: resistance. By exploring sexual assault and violence in their work, each writer resists the patriarchal systems of power that continue to support a misogynist justice system that supports abusers. In doing so, they reclaim their power and their voice. Created as a response to the Jian Ghomeshi case, writers including Joan Crate, Ashley-Elizabeth Best, and Beth Goobie are, as editor Sue Goyette explains, a "multitude, resisting." The collection could not be more timely. The work adds a new layer to the ever-growing #MeToo movement. Resistance underscores the validity of all women's experiences, and the importance of dignifying such experiences in voice, however that may sound. Because once survivors speak out and disrupt their pain, there is no telling what else they can do."–
OCLC: on1178897147
Keywords: 2000-2099; 21st century; Canadian poetry; Crimes against; Poetry; Sex crimes; Sexual abuse victims; Violence against; Women

Faire justice: moralisme progressiste et pratiques punitives dans la lutte contre les violences sexistes - Deck Marsault, Elsa (La Fabrique éditions, 2023)
Keywords: Bibliographie; Nettoyer; Restorative justice; Sexual minorities; Violence against; Women

‘Safe Spaces’: Experiences of Feminist Women-Only Space - Lewis, Ruth; Sharp, Elizabeth; Remnant, Jenni; Redpath, Rhiannon (Sociological Research Online, 2015)
The gendered nature of safety has been explored empirically and theoretically as awareness has grown of the pervasive challenges to women's safety. Notions of ‘safe space’ are frequently invoked in wider feminist environments (particularly, recently, in relation to debates about trans people's access to women's spaces), but are relatively neglected in academia. Indeed, despite a body of scholarship which looks at questions of gender, safety and space, relatively little attention has been paid to exploring the meaning of ‘safety’ for women and, particularly, the meaning and experience of spaces they consider to be ‘safe.’ Drawing on focus group data with 30 women who attended a two-day, women-only feminist gathering in the UK, this paper analyses experiences of what they describe as ‘safe space’ to explore the significance and meaning of ‘safety’ in their lives. Using their accounts, we distinguish between safe from and safe to, demonstrating that once women are safe from harassment, abuse and misogyny, they feel safe to be cognitively, intellectually and emotionally expressive. We argue that this sense of being ‘safe to’ denotes fundamental aspects of civic engagement, personhood and freedom.
Publisher: SAGE Publications Ltd
Keywords: Activism; Feminism; Safety; Space; Women; Women-Only